2020
DOI: 10.1371/journal.pone.0241771
|View full text |Cite
|
Sign up to set email alerts
|

Shifting seas, shifting boundaries: Dynamic marine protected area designs for a changing climate

Abstract: Marine protected areas (MPAs) are valuable tools for marine conservation that aim to limit human impacts on marine systems and protect valuable species or habitats. However, as species distributions shift due to ocean warming, acidification, and oxygen depletion from climate change, the areas originally designated under MPAs may bear little resemblance to their past state. Different approaches have been suggested for coping with species on the move in conservation. Here, we test the effectiveness of different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 44 publications
(53 reference statements)
0
19
0
Order By: Relevance
“…Considering MPA design may benefit from the inclusion and understanding of predator-prey dynamics (Micheli et al, 2004;Cashion et al, 2020), we also demonstrate how RSFs can be extended to examine spatially explicit relationships between marine predators and their prey. This was accomplished by deriving and averaging overlapping selection values from tiger sharks and from their potential prey, including juvenile green turtles, juvenile Caribbean reef sharks, juvenile lemon sharks, great barracuda (Sphyraena barracuda), horse-eye jack (Caranx latus), yellowtail snapper (Ocyurus chrysurus), and mutton snapper (Lutjanus analis) (Lowe et al, 1996;Simpfendorfer et al, 2001;O'Shea et al, 2015;Aines et al, 2018;Gallagher et al, 2021).…”
Section: Introductionmentioning
confidence: 64%
“…Considering MPA design may benefit from the inclusion and understanding of predator-prey dynamics (Micheli et al, 2004;Cashion et al, 2020), we also demonstrate how RSFs can be extended to examine spatially explicit relationships between marine predators and their prey. This was accomplished by deriving and averaging overlapping selection values from tiger sharks and from their potential prey, including juvenile green turtles, juvenile Caribbean reef sharks, juvenile lemon sharks, great barracuda (Sphyraena barracuda), horse-eye jack (Caranx latus), yellowtail snapper (Ocyurus chrysurus), and mutton snapper (Lutjanus analis) (Lowe et al, 1996;Simpfendorfer et al, 2001;O'Shea et al, 2015;Aines et al, 2018;Gallagher et al, 2021).…”
Section: Introductionmentioning
confidence: 64%
“…Adaptive management of this type also supports sustainable harvesting in changing environments, since they allow strategies to be continuously adjusted as needed. In general, flexible and dynamic strategies and measures (such as dynamic pro tected areas; Cashion et al 2020, Rassweiler et al 2020) are likely to be necessary as the climate continues to warm and environments become more variable.…”
Section: Harvesting In Fluctuating Environmentsmentioning
confidence: 99%
“…Tittensor et al (2019) described dynamic MPAs as "climateresponsive biodiversity closures." Given that climate change (climate-induced ocean warming) is affecting the distributions of marine species, MPAs, especially those with static boundaries, may lose their protection functions to achieve ecological objectives (Cashion et al 2020). Cashion et al (2020) found that while dynamic MPAs may provide ecological benefits, it is harder to apply this strategy in coastal areas due to the heightened conflict between marine protection and livelihood.…”
Section: Recommended Strategiesmentioning
confidence: 99%
“…Given that climate change (climate-induced ocean warming) is affecting the distributions of marine species, MPAs, especially those with static boundaries, may lose their protection functions to achieve ecological objectives (Cashion et al 2020). Cashion et al (2020) found that while dynamic MPAs may provide ecological benefits, it is harder to apply this strategy in coastal areas due to the heightened conflict between marine protection and livelihood. However, it is possible that dynamic MPAs could provide benefits in protecting many threatened species when applied to MPAs further offshore.…”
Section: Recommended Strategiesmentioning
confidence: 99%